教學原理教科書共通內容之研究：國小職前教師專業標準觀點The Study of Common Content on Principles of Teaching Textbooks: Perspective of Professional Standards for Preservice Elementary School Teachers - 劉唯玉Wei-Yu Liu; 陳蘋Pin Chen (Higher Education Foundation, 2010)
教育學程之課程長久以來有教育專業科目間聯繫不足，形成各科孤立學習的情況；以及教師教學專業自主，同樣的學科在不同教師的教導下，教學內容可能大不相同，因此無法預知學生在選擇各教育專業課程學習後，其教育專業能力能否達到職前教師專業標準。上述現象皆不利於保持或提升職前師資培育之品質。本研究比較中華民國師範教育學會所發展之「國民小學教師專業標準」及東華大學花師教育學院所發展之「國民小學職前教師專業準則」，得知國民小學職前師資教師專業標準之內涵。其次，分析中英文教學原理相關書籍，找出教學原理之九大共通主題內容，以及其應達到之職前教師專業標準。本研究結果將有助於國小師資培育學程「教學原理」共通內容之規劃與實施，提升師資培育課程之品質。 Education Program courses have long been complained for lack of relationship and isolated branches of learning; and for the reason of teachers' professional autonomy, different teachers teach the same subject may have different content. It is hard to predict whether the educational expertise can achieve pre-service teacher's professional standards or not. The above phenomenon is unfavorable to maintain or improve the quality of pre-service teacher education. This study finds the "Professional Standards for Preservice Elementary Teachers" by analyzing the differences between "Professional Standards for Elementary Teachers" and the "Professional Principles for Preservice Elementary Teachers". By comparing the common subjects among books of Chinese and English versions on Principles of Teaching and its relationship to the Professional Standards for Preservice Elementary Teachers, the researchers suggest a common teaching goal and the course content for Principles of Teaching, which would be helpful in planning and implementing a common content for "Teaching Principles" to enhance the quality of teacher education courses.